Tingkat Kepuasan Kerja Dilihat Dari Perspektif Lingkungan Kerja Sosial dan Pengembangan Karir - Rahmadi, Ryan; Senen, Syamsul Hadi; Sumiyati, Sumiyati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2018)
The purpose of this study was to determine the effect of physical work environment and work ability on employee performance. This study was conducted in a span of less than one year, the research design used was a cross-sectional method. This study uses a descriptive and verification approach with the explanatory survey method. 92 respondents were selected as samples using probability sampling. The research questionnaire is used as a research instrument to collect data from respondents, and the data analysis technique used is multiple linear regression. The findings obtained are physical work environment and work ability significantly influence employee performance. differences found in objects and research methods, populations and research samples, research periods, measurement tools and research results, and sources of theory from foreign journals and foreign books